2021
DOI: 10.31234/osf.io/56kcp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A longitudinal study of mental health in adolescents before and during the COVID-19 pandemic

Abstract: Objective Although cross-sectional studies have shown that the COVID-19 pandemic has negativelyaffected the mental health of adolescents, the effect of the pandemic on adolescents with pre-pandemicsymptoms is unclear. We therefore tested the hypothesis that adolescents had increased emotional andbehavioral problems during the lockdowns imposed during the pandemic.Method This study included three measurements in a prospective cohort of 1022 adolescentswho were oversampled based on their high risk of developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Overall, we can conclude that the positive changes to a child’s life due to the first lockdown—the relationships among the family members, the time spent watching TV, and parental evaluation of the child’s mental health and the stress caused by COVID-19 restrictions—could play crucial role to the change in the mood state of the child. These results are aligned with the results of relevant studies found on the literature that incorporated pre-pandemic clinical samples or population-based cohorts of children at high risk for transition from subclinical to clinically significant levels of psychopathology [ 72 , 73 , 74 ]. Moreover, the finding that that most of the children and youths managed to maintain stable mood (63.04%: 469 out of 744) or even have positive mood change (14.25%: 106 out of 744) may be related to the concept of resilience.…”
Section: Discussionsupporting
confidence: 83%
“…Overall, we can conclude that the positive changes to a child’s life due to the first lockdown—the relationships among the family members, the time spent watching TV, and parental evaluation of the child’s mental health and the stress caused by COVID-19 restrictions—could play crucial role to the change in the mood state of the child. These results are aligned with the results of relevant studies found on the literature that incorporated pre-pandemic clinical samples or population-based cohorts of children at high risk for transition from subclinical to clinically significant levels of psychopathology [ 72 , 73 , 74 ]. Moreover, the finding that that most of the children and youths managed to maintain stable mood (63.04%: 469 out of 744) or even have positive mood change (14.25%: 106 out of 744) may be related to the concept of resilience.…”
Section: Discussionsupporting
confidence: 83%
“…Overall, we can conclude that the positive changes to child's life due to the 1 st lockdown, the relationships among the family members, the time spent on TV and parental evaluation of the child's mental health and the stress caused by COVID-19 restrictions could play crucial role to the change of the mood state of the child. These results are aligned with the results of relevant studies found on the literature that incorporated pre-pandemic clinical samples or population-based cohorts of children at high risk for transition from subclinical to clinically significant levels of psychopathology [61][62][63]. Moreover, the finding that that most of the children and youths managed to maintain stable mood (63.04%: 469 out of 744) or even have positive mood change (14.25%: 106 out of 744) may be related to the concept of resilience.…”
Section: Discussionsupporting
confidence: 83%
“…As far as we know, only one study compared adolescent mental health pre-COVID-19 with various COVID-19 phases. This prospective study was conducted among adolescents with a high risk of developing psychopathology in the Netherlands (Bouter et al, 2021)…”
Section: The Importance Of Comparing Different Phases Of Covid-19mentioning
confidence: 99%
“…As far as we know, only one study compared adolescent mental health pre‐COVID‐19 with various COVID‐19 phases. This prospective study was conducted among adolescents with a high risk of developing psychopathology in the Netherlands (Bouter et al., 2021 ). Results revealed increases in depressive symptoms when comparing scores before COVID‐19 with scores during the initial COVID‐19 phase (April 2020), but also when comparing the initial COVID‐19 phase with the prevailing COVID‐19 phase (January 2021).…”
Section: Introductionmentioning
confidence: 99%